Social behaviour and crop raiding in Chacma baboons of the Suikerbosrand Nature Reserve - Pahad, Govan (My University, 2011)
Conflict between baboons and humans is a common occurrence in many places where baboons exist in close proximity to cultivated land. This study examines patterns of raiding by baboons, farmer retaliation, and potential behavioural responses of baboons to that retaliation in and around the Suikerbosrand Nature Reserve, South Africa. Recent years have seen a rising baboon population and increasing complaints from farmers in the area about baboons raiding their farmland, leading to concerns that the population may have outgrown the resources available within the reserve. This study consists of three parts: an examination of patterns of space use by baboons, using data from GPS collars fitted to one baboon in each of 10 troops in the reserve; an examination of the behaviour of baboons in 9 of these troops, using data gained though direct observation of troops within the reserve; and an examination of patterns of raiding and farmer retaliation, using data from questionnaires sent to land owners surrounding the reserve. The data revealed that the troops appeared to be responding to resource scarcity and the opportunity to raid in a variety of ways. Some troops appeared to be raiding farmland intensively on short forays out of the reserve, while using the reserve as a refuge, indicated by small amounts of time spent outside the reserve, high levels of overlap between troops and low levels of foraging within the reserve. Other troops appeared to be shifting their home ranges out of the reserve to forage on fallow land, while also raiding farmland to some extent, indicated by large amounts of time spent outside the reserve, low levels of overlap between troops, and low levels of foraging within the reserve. Two of the troops studied apparently did not raid, as they never left the reserve. Data from the questionnaires suggest that, while raiding is stimulated by food scarcity in the dry season, baboons raid maize and beans whenever available, seemingly preferring these crops over natural forage. While some farmers are responding to raiding with lethal retaliation against baboons, the effects of this on the social structure of the troops are unclear due to low sample sizes of behavioural data. This study demonstrates some of the behavioural responses of baboons to raiding and farmer retaliation, and some of the different responses available to baboon troops facing a scarcity of natural food together with the opportunity to raid farmland. Based on my findings, I also provide recommendations to farmers and the Suikerbosrand management aimed at reducing baboon human conflict in the area.